The Black Civil War soldier : a visual history of conflict and citizenship - Willis, Deborah, 1948- (NYU series in social and cultural analysis., 2021)
"A stunning collection of stoic portraits and intimate ephemera from the lives of Black Civil War soldiers Though both the Union and Confederate armies excluded African American men from their initial calls to arms, many of the men who eventually served were black. Simultaneously, photography culture blossomed--marking the Civil War as the first conflict to be extensively documented through photographs. In The Black Civil War Soldier, Deb Willis explores the crucial role of photography in (re)telling and shaping African American narratives of the Civil War, pulling from a dynamic visual archive that has largely gone unacknowledged. With over seventy images, The Black Civil War Soldier contains a huge breadth of primary and archival materials, many of which are rarely reproduced. The photographs are supplemented with handwritten captions, letters, and other personal materials; Willis not only dives into the lives of black Union soldiers, but also includes stories of other African Americans involved with the struggle--from left-behind family members to female spies. Willis thus compiles a captivating memoir of photographs and words and examines them together to address themes of love and longing; responsibility and fear; commitment and patriotism; and--most predominantly--African American resilience. The Black Civil War Soldier offers a kaleidoscopic yet intimate portrait of the African American experience, from the beginning of the Civil War to 1900. Through her multimedia analysis, Willis acutely pinpoints the importance of African American communities in the development and prosecution of the war. The book shows how photography helped construct a national vision of blackness, war, and bondage, while unearthing the hidden histories of these black Civil War soldiers. In combating the erasure of this often overlooked history, Willis asks how these images might offer a more nuanced memory of African-American participation in the Civil War, and in doing so, points to individual and collective struggles for citizenship and remembrance."--Publisher description.